The Advertising Business: Operations, Creativity, Media Planning, Integrated Communications - Jones, John Philip (SAGE Publications, Incorporated, 1999)
This authoritative and comprehensive handbook of successful advertising practices addresses such aspects of the business as: agency operation, creativity, media planning, operations and speciality advertising. The distinguished contributors reflect a global mix of academic and professional backgrounds, and most chapters - complemented by a few adaptations of classic articles - have been specifically written for this volume. The result is a single `knowledge bank′ of theory and practice for advertising students and professionals.
https://katalog.adlr.link/Record/76-EBC996945